THE USE OF PICTURE AND PICTURE MODEL ON MOTIVATION, MATHEMATICAL COMMUNICATION SKILLS, AND MATHEMATICS LEARNING OUTCOMES - Haerunnisa, Etty Arfa; Syamsuddin, Agustan; Saleh , Sitti Fithriani (Jurnal Pendidikan (Teori dan Praktik), 2024)
The purpose of the study is to comprehend different motivational factors, mathematical communication abilities, and learning outcomes produced by Fourth-grade students using the Picture and Picture siswa. This study's methodology is essentially an experiment. Nonequivalent Control Group Design is the tool for running a quasi-experiment in this study. 53 people make up the sample size in this study; of these, 29 people are from the control group and 24 people are from the experimental group. Tes Hasil Belajar is a method for gathering data that is used to improve learning outcomes and mathematical communication skills, as well as questioner to improve learning motivation and documentation. The techniques for data analysis that are used are descriptively applied statistics, inferential analysis, and hypothesis testing. Ho was eliminated and H1 was cited as the study's findings after the multivariate test with a level of significance of sig. 0.000 to 0.05, which denotes the presence of a statistically significant difference.